Analisis Beban Kerja untuk Menentukan Jumlah Tenaga Kerja Optimal Dalam Upaya Meningkatkan Produktivitas - Ramdhan Syafri Syamsudin; Erni Puspanantasari Putri (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
UD. Gajah Delta is a manufacturing company whose main products are rantang and bakso steamers. Based on the current situation in the field, UD Gajah Delta has difficulty meeting market demand. Gajah Delta berjuang untuk memenuhi permintaan pasar. This is thought to be due to an imbalance in workload between workstations, as well as suboptimal planning of the number of employees. The aim of this study is to determine the optimal number of employees to meet customer demand. Based on the workload measurement using the Full Time Equivalent (FTE) method, two workstations were found to be normal: the cutting station (1.24) and the finishing station (1.22). However, the workstations for lid production (2.68) and sieve production (4.25) were categorised as overload. Meanwhile, the handle production station had an FTE value of 5.77 and the pot body production station had an FTE value of 8.98. Therefore, it is necessary to increase the number of employees at the stations for making handles and making the body of the steamer.